Spinocerebellar ataxia 12 patients have better quality of life than spinocerebellar ataxia 1 and 2 - Surekha Dabla; Divyani Garg; Rajeev Aggarwal; Nand Kumar; Mohammad Faruq; Roopa Rajan; Garima Shukla; Vinay Goyal; Ravindra Mohan Pandey; Achal Kumar Srivastava (Annals of Indian Academy of Neurology, 2022)
Background: Spinocerebellar ataxia is a neurodegenerative disease. Information on comparative assessment of quality of life (QoL) among SCAs, particularly SCA 12, is scarce. We aimed to compare health-related QoL in SCA 1, 2 and 12. Methods: We conducted a cross-sectional study among individuals with genetically-confirmed SCAs. Ataxia severity was assessed using Brief Ataxia Rating Scale (BARS), independence in activities of daily living (ADL) using Katz index (Katz ADL) and depression using Beck's Depression Inventory-II (BDI-II). QoL was assessed via Short Form Health Survey version 2.0 (SF-36). Results: We enrolled 89 individuals (SCA1 = 17, SCA2 = 43, SCA12 = 29; 56% males). Mean age at onset (41.0 ± 11.6 for SCA12 versus 24.9 + 7.0 for SCA1 and 28.8 ± 9.8 years for SCA2) was significantly higher among SCA12. SCA12 had lower BARS (mean score 4.1 ± 4.5 versus 10.6 ± 4.6 for SCA1 and 12.5 ± 4.5 for SCA2). SCA12 scored better on all SF-36 subdomains including Physical (PCS) and Mental Component Summary (MCS) scores. PCS score amongst SCA12 was 44.4 ± 9.0 versus 30.4 ± 9.1 for SCA1 and 33.3 ± 8.9 for SCA2. MCS score for SCA12 was 51.4 ± 11.4 versus 41.8 ± 11.5 for SCA1 and 41.8 ± 11.2 for SCA2. SCA12 had lower mean BDI scores (5.0 ± 6.0) versus SCA1 (9.5 ± 11.6) and SCA2 (10.9 ± 10.3). BARS and BDI emerged as significant predictors of most SF-36 subdomains. Conclusions: Our study suggests that despite older age and comparable disease duration, SCA12 patients experience better QoL, less severe depression and ataxia versus SCA1 and SCA2. Severity of ataxia and depression are significant predictors of QoL among the three SCA types.